الأحكام القانونية للوفاء بالسفتجة في القانون التجاري الجزائري - أيوب بوتمجت (My University, 2025)
Summary: The bill of exchange represents a vital instrument in Algerian law to ensure the fulfillment of financial obligations within the commercial framework, where the legal system establishes strict principles governing this fulfillment while allowing limited flexibility to accommodate exceptional circumstances. The diversity of legal guarantees whether negotiable, contractual, or personal reflects the legislator’s effort to strike a precise balance between protecting parties’ rights and enhancing legal certainty in commercial transactions. Furthermore, the legal mechanisms addressing refusal to pay, notably protest and recourse, reveal an integrated system aimed at safeguarding the holder’s rights and ensuring effective enforcement, despite the pressing need to reform certain provisions to overcome practical challenges, especially regarding proof of payment and extinguishment of obligations. Reviewing and updating this legal framework is imperative to keep pace with economic developments, thereby strengthening trust and legal stability, and consolidating the bill of exchange’s role as a reliable and efficient payment instrument in modern commercial dealings. ............................... ملخص : تُجسد السفتجة في القانون الجزائري أداة حيوية لضمان الوفاء بالالتزامات المالية ضمن الإطار التجاري، حيث يرسّخ النظام القانوني مبادئ صارمة تنظم تنفيذ هذا الوفاء، مع إقرار مرونة محدودة تتيح استجابة واقعية للظروف الطارئة. ويعكس تنوع الضمانات القانونية، من صرفية واتفاقية وشخصية، سعي المشرع لتحقيق توازن دقيق بين حماية حقوق الأطراف وتعزيز الأمن القانوني في المعاملات التجارية. كما تكشف الآليات القانونية المرتبطة بالامتناع عن الوفاء، لا سيما الاحتجاج والرجوع الصرفي، عن نظام متكامل يهدف إلى صون حقوق الحامل وضمان فعالية التنفيذ، رغم الحاجة الملحة لتطوير بعض النصوص القانونية لتجاوز الإشكالات التطبيقية، خاصة في ميدان إثبات الوفاء وانقضاء الالتزام. إن مراجعة هذا الإطار القانوني وتحديثه تُعد ضرورة حتمية لمواكبة التطورات الاقتصادية، مما يساهم في تعزيز الثقة والاستقرار القانوني، ويُرسخ مكانة السفتجة كأداة دفع موثوقة وفعالة في المعاملات التجارية الحديثة. ................................... Resumé : La lettre de change constitue un instrument essentiel dans le droit algérien pour garantir l’exécution des obligations financières dans le cadre commercial. Le système juridique y applique des principes stricts tout en permettant une certaine souplesse pour répondre à des circonstances exceptionnelles. La diversité des garanties juridiques — qu’elles soient négociables, contractuelles ou personnelles — reflète la volonté du législateur de trouver un équilibre précis entre la protection des droits des parties et la sécurité juridique des transactions commerciales. De plus, les mécanismes juridiques relatifs au refus de paiement, notamment le protêt et le recours, traduisent un dispositif intégré visant à préserver les droits ;du porteur et à garantir une exécution efficace. Toutefois, certaines dispositions nécessitent une réforme urgente afin de surmonter les difficultés pratiques, en particulier celles liées à la preuve du paiement et à l’extinction des obligations. Une révision de ce cadre juridique s’impose pour suivre l’évolution économique, renforcer la confiance et la stabilité juridique, et consolider le rôle de la lettre de change en tant qu’instrument de paiement fiable et performant dans les échanges commerciaux modernes.
Keywords: Keywords • Bill of exchange • Payment • Algerian commercial law • Commercial papers • Cambial obligation • Refusal of payment • Legal protection; الكلمات المفتاحية : • السفتجة • الوفاء • القانون التجاري الجزائري • الأوراق التجارية • الالتزام الصرفي • الامتناع عن الدفع • الحماية القانونية; Mots-clés • Lettre de change • Paiement • Droit commercial algérien • Effets de commerce • Obligation cambiaire • Refus de paiement • Protection juridique